2016
DOI: 10.1128/iai.00416-16
|View full text |Cite
|
Sign up to set email alerts
|

Infant Mouse Model for the Study of Shedding and Transmission during Streptococcus pneumoniae Monoinfection

Abstract: One of the least understood aspects of the bacterium Streptococcus pneumoniae (pneumococcus) is its transmission from host to host, the critical first step in both the carrier state and the disease state. To date, transmission models have depended on influenza A virus coinfection, which greatly enhances pneumococcal shedding to levels that allow acquisition by a new host. Here, we describe an infant mouse model that can be utilized to study pneumococcal colonization, shedding, and transmission during bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 30 publications
3
102
0
Order By: Relevance
“…We had previously reported that transmission of strain T4S during mono-infection requires a high ratio (~1:1) of ‘‘index’’ pups colonized at day 4 of age to uncolonized ‘‘contact’’ littermates (Zafar et al, 2016). Under these experimental conditions, T4S transmission from index to contact pups was observed in 28% of pups (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We had previously reported that transmission of strain T4S during mono-infection requires a high ratio (~1:1) of ‘‘index’’ pups colonized at day 4 of age to uncolonized ‘‘contact’’ littermates (Zafar et al, 2016). Under these experimental conditions, T4S transmission from index to contact pups was observed in 28% of pups (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Strains deficient in Ply hemolytic activity may escape innate immune surveillance at the expense of a lower transmission rate. Our study depended on a model where high levels of shedding are needed to detect transmission from pup to pup (Zafar et al, 2016). Transmission rates during natural carriage could be higher or lower, and this could reflect the volume or type of secretions the organism induces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This tight population bottleneck during transmission would explain the need for large numbers of shed pneumococci for at least one to be successful in reaching a new host. Accordingly, increasing total shedding per cage by increasing the proportion of colonized index pups per cage to 50% made transmission to ∼30% of contacts possible without the need for IAV co-infection 14 .…”
Section: Transmission Of S Pneumoniaementioning
confidence: 99%